2020
DOI: 10.1101/2020.05.21.20108704
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 in Bangladesh: Measuring differences in individual precautionary behaviors among young adults

Abstract: Aim: The novel coronavirus disease 2019 (COVID-19) has already hit Bangladesh, and various control measures have been taken to flatten the epidemic curve. Due to the current demographic distribution in Bangladesh, young adults are vital to the demography of the country. Therefore, their precautionary behavior is very important to ensure the success of preventive policies. This exploratory study examined the differences in the adoption of precautionary behaviors among young adults, and estimated and compared th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 43 publications
4
5
0
1
Order By: Relevance
“…Knowledge played only a marginally significant role. This is in line with previous literature where a significant effect had been found in the case of HIV (DiClemente et al, 1986 , 1988 ), but not in the case COVID-19 (Imtiaz et al, 2020 ). Contrary to Lunn et al ( 2020 ) and Lammers et al ( 2020 ), we did not find a significant effect of knowledge on exponential growth (this, however, could simply be a sample size effect).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Knowledge played only a marginally significant role. This is in line with previous literature where a significant effect had been found in the case of HIV (DiClemente et al, 1986 , 1988 ), but not in the case COVID-19 (Imtiaz et al, 2020 ). Contrary to Lunn et al ( 2020 ) and Lammers et al ( 2020 ), we did not find a significant effect of knowledge on exponential growth (this, however, could simply be a sample size effect).…”
Section: Resultssupporting
confidence: 93%
“…Similar results have also been found in the context of influenza A/H1N1 (Lin et al, 2011 ), see also (Akan et al, 2010 ). In the case of COVID-19, the evidence is so far mixed: while (Imtiaz et al, 2020 ) finds a significant positive effect of education on precautionary behavior, they did not find an effect of better general knowledge about COVID-19. A better understanding of the nature of exponential growth, however, can motivate social distancing, as has been shown in controlled experiments (Lammers et al, 2020 ; Lunn et al, 2020 ).…”
Section: Introductionmentioning
confidence: 94%
“…Our results were similar to a study during Covid-19 (34). According to the some studies during a pandemic; compliance rates were associated with some demographic characteristics: female and healthcare workers had higher overall compliance scores than male and other occupational groups (34,35). Compared with the general population, health care providers have higher health literacy as well as, due to duty calls, they are more likely to come in contact with COVID-19 carriers putting them at a greater risk of contracting the infection and spreading it to others (36).…”
Section: Discussionsupporting
confidence: 92%
“…Our findings demonstrated that engagement in the preventive behaviors was significantly higher in female and health workers than other participants. Our results were similar to a study during Covid-19 (34). According to the some studies during a pandemic; compliance rates were associated with some demographic characteristics: female and healthcare workers had higher overall compliance scores than male and other occupational groups (34,35).…”
Section: Discussionsupporting
confidence: 90%
“…Only one cross-country research [52] has been conducted with the purpose of sustainable development, where correlation among confirmed cases and environmental and demographic factors of four different countries were calculated and compared. The study conducted by Imtiaz et al [79] in the context of a developing country (Bangladesh), explored the factors for the adoption precautionary measurements and authors in [80] exploit the challenges faced by a specific subset of the population: the Rohingya refugees. Other cross-country research studies, and contextual studies focusing on a specific demographic can be pursued in the future to determine if the virus spread depends on environmental factors.…”
Section: Future Research Opportunitiesmentioning
confidence: 99%